The new(s) alternative? a media content and audience study on Rappler vis-a-vis Inquirer.net - Marquez, Ana Michaela Ignacio 1992-; Perez, Kyla Trischia Reyes; Umali, Violeda A., Ph.D.; University of the Philippines. College of Mass Communication (2014)
"This study examines Rappler's claim as an alternative news source by comparing it with the news website of the Philippine Daily Inquirer in terms of a) website features and news coverage, and b) demographic characteristics and political involvement of their readers. The Elaboration Likelihood Model and Framing Theory were used to build the theoretical framework. The researchers analyzed 20 news articles and six different sections from the two sites to identify dominant news slants and to find out which news website features were present. Using purposive sampling, frequent readers of Rappler (n=61) and Inquirer.net (n=59) were selected to answer a survey about their use of their chosen news sites and their political involvement. Three readers from each site were interviewed about their political leanings to supplement the quantitative data. The researchers discovered that there were few differences between the two sites in terms of website features and news presentation. Their respective readers also did not differ much in terms of demographic characteristics and participation in online and offline political activities. In sum, although Rappler brands itself as an alternative news source and plays a role in influencing its readers' online political activity, it is already very similar to mainstream sites and has yet to expand its influence to political activity offline."
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Alternative mass media -- Philippines; News Web sites -- Evaluation -- Philippines; Electronic newspapers -- Evaluation -- Philippines; Content analysis (Communication).